Exploration of Local Knowledge Traditional Medicine and Food Ingredients of The Anak Dalam Tribe, Duano, Kerinci As a Source of Public Health Knowledge - Mustakim, Ardi; Nirmala, Nirmala; Anattri, Lega; Mulyadi, Elvaro Islami; Arfina, Nabila (PPSDP International Journal of Education, 2023)
The purpose of this study was to explore local knowledge and traditional food ingredients for the Anak Dalam, Duano and Kerinci people, especially those related to traditional medicine and food ingredients for each Jambi tribes. The Anak Dalam, Duano and Kerinci tribes have a rich cultural heritage, with local knowledge on spices and ingredients passed down from generation to generation. This study examines local wisdom as a source of public health. This type of qualitative research with an ethnographic approach to data collection was carried out through observation, interviews, focused discussions (FGD) and documentation with the Anak Dalam, Duano and Kerinci ethnic community. As a result, we found that the Anak Dalam tribe has Basale treatment, Duano has the Kelung ritual, and Kerinci has a lot of knowledge about local medicines and different foods, one of which is Betemas/Tasapa. In addition, the traditional diet of the Suku Anak Dalam, Duano and Kerinci tribe emphasizes the use of locally available ingredients for their nutritional and medicinal properties. This study highlights the importance of local knowledge in public health information resources. In addition, traditional food ingredients provide information about sustainable diets and potential sources of new compounds, this research contributed in finding the novelty of etnosains and etnofood Jambi tribes. This research concludes that raising awareness through the documentation of traditional knowledge Jambi's indigenous people is important for the preservation and regeneration of cultural heritage. As result, Studying the local knowledge of traditional medicine and ingredients of the Anak Dalam, Duano, Kerinci tribes are valuable insights for public health.